Food Oligosaccharides 2014
DOI: 10.1002/9781118817360.ch19
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Food Bioactive Oligosaccharides by Thin‐Layer Chromatography

Abstract: IntroductionCarbohydrates are normally naturally occurring organic polyhydroxyl substances expressed by the empirical formula (CH 2 O) n, and their derivates. Sugars in foods and food products can be present as simple sugars -monosaccharides with low molecular weight and consisting of a single basic sugar unit -or as complex sugars -oligosaccharides and polysaccharides. Oligosaccharides are complex saccharides with a degree of polymerization (DP) of 2-9 and an intermediate molecular weight in which the monosac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…However, in our study, the TLC chromatogram had shown distinct spots of oligosaccharides derived from the exopolysaccharide of Nitzschia palea . The optimized mobile phase for TLC was chloroform, acetic acid, and water in the ratio of 6:7:1 reported according to Reiffova 36 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the TLC chromatogram had shown distinct spots of oligosaccharides derived from the exopolysaccharide of Nitzschia palea . The optimized mobile phase for TLC was chloroform, acetic acid, and water in the ratio of 6:7:1 reported according to Reiffova 36 .…”
Section: Discussionmentioning
confidence: 99%